Distribution, host plant affiliation, phenology, and phylogeny of walnut‐infesting Rhagoletis flies (Diptera: Tephritidae) in Mexico. (17th October 2013) - Rull, Juan; Aluja, Martin; Tadeo, Eduardo; Guillen, Larissa; Egan, Scott; Glover, Mary; Feder, Jeffrey L.
<x xml:space="preserve">Abstract</x> Many taxa of Nearctic origin have diversified in the subtropical highlands of Mexico. In particular, flies in the genus Rhagoletis have undergone episodes of isolation and gene flow during Pleistocene glaciations and post‐glacial times that have produced lineage differentiation and reproductive isolation. To reach a better understanding of the phylogeography of the genus Rhagoletis, a host plant survey of the walnut‐infesting Rhagoletis suavis species group was conducted across sixteen states comprising 34 different collecting sites in Mexico over a 9‐year period. Five species of Juglans were found to be infested by three species of walnut‐attacking Rhagoletis flies. Several species of parasitoids were also recovered from collections, but in contrast to their walnut fly hosts, they revealed little evidence for host or geographic subdivision. There was no consistent difference in mean eclosion time between walnut fly species or populations associated with different host walnuts in Mexico, unlike the case for other Rhagoletis species, in which allochronic isolation arising from variation in diapause timing is a major ecological adaptation, reproductively isolating flies. We compare the distribution of R. suavis flies in Mexico with those of other Rhagoletis species attacking hawthorns and cherries, and discuss its implications for population divergence and speciation. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 110, 765–779.